Photosensitizer Adhered to Cell Culture Microplates Induces Phototoxicity in Carcinoma Cells. (23rd December 2012) - Ziegler, Verena; Kiesslich, Tobias; Krammer, Barbara; Plaetzer, Kristjan
Abstract : In vitro experiments in plastic receptacles are the basis of characterization of new photosensitizers (PSs) for the photodynamic therapy. We recently reported that lipophilic PSs adhere to cell culture microplates in a kinetic-like manner (Engelhardt et al., 2011). In the current study, we examined the interaction and phototoxic effects of the microplate-adhered PS in cancer cells. Therefore, we preloaded microplates with hypericin, Foscan, PVP-hypericin, or aluminum (III) phthalocyanine tetrasulfonate chloride (AlPCS4 ) for 24 hours and measured the PS distribution after addition of A431 human carcinoma cells: following another 24 hours up to 68% of hypericin were detected in the cell fraction. The hydrophilic PVP-hypericin and AlPCS4 also diffused into the cells, but the quantities of PS adherence were considerably lower. Microplate-adhered Foscan appeared not to be redistributed. In contrast to the hydrophilic PSs, the cellular phototoxicity of microplate-adhered lipophilic PS was high, independent of whether the PS (i) was pre-loaded onto microplates or (ii) added simultaneously with the cells or (iii) one day after cell seeding. Based on these results, we suggest testing lipophilic PS dyes for their adherence to microplates. Furthermore, the ability of plastic materials to (reversibly) store PSs might represent a new approach for the PS delivery or the development of antimicrobial coatings.